Is the polymorphism at position -1082 of IL-10 gene associated with visceral leishmaniasis? - Mehrdad Hajilooi; Alireza Ahmadi; Pegah Lotfi; Mohammad Matini; Davood Jafari; Ahad Bazmani; Mohammad Momeni (Tehran University of Medical Sciences, 2014)
Immune responses play critical roles in the leishmaniasis eradication. IL-10 is a key regulator of immune responses, and the polymorphisms within its promoter region are associated with alteration in its expression. Therefore, this study was designed to examine the correlation between polymorphism at the -1082 position of the IL-10 gene and visceral leishmaniasis (VL).The IL-10 -1082 polymorphism and anti-Leishmania antibody titration were examined in 110 patients with clinical presentation of VL and seropositive for the Leishmania (group 1), 74 seropositive patients but without clinical presentation (group 2) and 113 healthy controls (group 3) using the PCR-RFLP and immunofluorescence techniques, respectively.The polymorphism at IL-10 -1082 (A/G) position was significantly associated with VL and A/G genotype was significantly higher in VL patients when compared to the groups 2 and 3 (P< 0.001). However, the results demonstrated that the A and G alleles were not associated with VL (P= 0.263).Previous investigations have shown that the polymorphism at the -1082 position of the IL-10 gene can influence its expression and also it has been proved that IL-10 level was increased during VL. Our results suggest that the A/G genotype may be considered as a risk factor for VL.